Splicing defects and CRISPR-Cas9 correction in isogenic homozygous photoreceptor precursors harboring clustered deep-intronic ABCA4 variants - Pietro De Angeli; Arturo Flores-Tufiño; Katarina Stingl; Laura Kühlewein; Eleonora Roschi; Bernd Wissinger; Susanne Kohl (Elsevier, 2024)
Splicing defects from deep-intronic variants significantly contribute to the mutational spectrum in ABCA4-associated inherited retinal diseases, necessitating functional validation for their pathological classification. Typically, minigene assays in HEK293(T) can qualitatively assess splicing defects, yet they often fail to quantitatively reproduce the resulting mis-splicing patterns, leaving uncertainty on severity and pathogenicity. As a potential cellular model derived from patient cells, photoreceptor precursor cells (PPCs) play a pivotal role in assessing the severity of specific splicing mutations. Nevertheless, the accessibility of biosamples is commonly constrained, and their establishment is costly and laborious. In this study, we combined and investigated the use of a minigene assay and isogenic PPCs, as superior qualitative and more accessible cellular models for the assessment of splicing defects. Specifically, we focused on the clustered c.5196+1013A>G, c.5196+1056A>G, and c.5196+1216C>A deep-intronic variants in intron 36 of ABCA4, comparing their resulting (mis)splicing patterns in minigene-transfected cells and isogenic CRISPR-Cas9-knocked-in PPCs harboring these pathogenic variants in homozygous state. Moreover, we demonstrate the successful correction of these three splicing defects in homozygous mutant PPCs using a single pair of guide RNAs to target Cas9 cleavage, thereby identifying an efficient gene editing strategy for therapeutic applications.